KESIAPAN LINGKUNGAN BELAJAR ANAK DI LEMBAGA PENDIDIKAN ANAK USIA DINI BANJARMASIN - Auliya, Alfiana Falan Syarri; Fashlah, Anggita Gunati; Wahyudi, Mohammad Dani (Early Stage, 2025)
This study aims to explore the condition of learning environments in early childhood education (ECE) institutions in Banjarmasin. The study used a descriptive qualitative observational method involving 19 PAUD institutions consisting of kindergartens, Raudhatul Athfal and playgroups. Data were collected through direct observation of physical facilities, including play areas, ventilation, spatial arrangement, and availability of toys and reading booksthatsupport children's development. Thematic analysis based on data needs was used in thisstudy. The resultsshow that most institutions have met the standardsfor environmental arrangements, such as the presence of outdoor play areas, toys that support exploration, and the provision of books for basic literacy. However, some institutions still need to improve teacher-child ratios and more consistent timings. Good environmental arrangements can facilitate children's exploration and development optimally. Therefore, PAUD institutions need to continue to improve the organisation of the learning environment to achieve maximum learning objectives.Keywords: learning environment, environment arrangement, early childhood